Functional Expression of Gloeobacter Rhodopsin in PSI-Less Synechocystis sp. PCC6803 - Chen, Que; Arents, Jos; Schuurmans, J. Merijn; Ganapathy, Srividya; de Grip, Willem J.; Cheregi, Otilia; Funk, Christiane; Branco dos Santos, Filipe; Hellingwerf, Klaas J. (Frontiers in Bioengineering and Biotechnology, 2019)
The approach of providing an oxygenic photosynthetic organism with a cyclic electron transfer system, i.e., a far-red light-driven proton pump, is widely proposed to maximize photosynthetic efficiency via expanding the absorption spectrum of photosynthetically active radiation. As a first step in this approach, Gloeobacter rhodopsin was expressed in a PSI-deletion strain of Synechocystis sp. PCC6803. Functional expression of Gloeobacter rhodopsin, in contrast to Proteorhodopsin, did not stimulate the rate of photoheterotrophic growth of this Synechocystis strain, analyzed with growth rate measurements and competition experiments. Nevertheless, analysis of oxygen uptake and—production rates of the Gloeobacter rhodopsin-expressing strains, relative to the ΔPSI control strain, confirm that the proton-pumping Gloeobacter rhodopsin provides the cells with additional capacity to generate proton motive force. Significantly, expression of the Gloeobacter rhodopsin did modulate levels of pigment formation in the transgenic strain.